PENGARUH KEPERCAYAAN DIRI, KECERDASAN EMOSIONAL, LINGKUNGAN KELUARGA, DAN LINGKUNGAN SEKOLAH TERHADAP PRESTASI BELAJAR SISWA MELALUI DISIPLIN BELAJAR SEBAGAI VARIABEL INTERVENING KELAS XI/FASE F PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 5 PADANG - Desparni, Antika; Desi Areva; Dina Amaluis (Journal of Practice Learning and Educational Development, 2026)
This study aims to determine the influence of self-confidence, emotional intelligence, family environment, and school environment on students’ academic achievement through learning discipline as an intervening variable in Grade XI/Phase F Economics subject at SMA Negeri 5 Padang. This type of research is associative. The population in this study consisted of 79 Grade XI/Phase F students in the Economics subject at SMA Negeri 5 Padang. The sampling technique used was stratified random sampling. The results of this study show that:1) There is a significant influence of self-confidence on learning discipline, indicated by a path coefficient value of 0.226. This coefficient is significant because the t-count value of 2.417 > t-table 1.66437 with a significance value of 0.018 < α = 0.05. This means H0 is rejected and Ha is accepted. 2) There is a significant influence of emotional intelligence on learning discipline, indicated by a path coefficient value of 0.278. This coefficient is significant because the t-count value of 2.975 > t-table 1.66437 with a significance value of 0.004 < α = 0.05. This means H0 is rejected and Ha is accepted. 3) There is a significant influence of the family environment on learning discipline, indicated by a path coefficient value of 0.414. This coefficient is significant because the t-count value of 4.414 > t-table 1.66437 with a significance value of 0.000 < α = 0.05. This means H0 is rejected and Ha is accepted. 4) There is a significant influence of the school environment on learning discipline, indicated by a path coefficient value of 0.278. This coefficient is significant because the t-count value of 2.968 > t-table 1.66437 with a significance value of 0.004 < α = 0.05. This means H0 is rejected and Ha is accepted. 5) There is a significant influence of learning discipline on academic achievement, indicated by a path coefficient value of 0.322. This coefficient is significant because the t-count value of 11.429 > t-table 1.66437 with a significance value of 0.000 < α = 0.05. This means H0 is rejected and Ha is accepted. 6) There is a significant influence of self-confidence on academic achievement, indicated by a path coefficient value of 0.370. This coefficient is significant because the t-count value of 15.741 > t-table 1.66437 with a significance value of 0.000 < α = 0.05. This means H0 is rejected and Ha is accepted. 7) There is a significant influence of emotional intelligence on academic achievement, indicated by a path coefficient value of 0.381. This coefficient is significant because the t-count value of 15.943 > t-table 1.66437 with a significance value of 0.000 < α = 0.05. This means H0 is rejected and Ha is accepted. 8) There is a significant influence of the family environment on academic achievement, indicated by a path coefficient value of 0.410. This coefficient is significant because the t-count value of 16.077 > t-table 1.66437 with a significance value of 0.000 < α = 0.05. This means H0 is rejected and Ha is accepted. 9) There is a significant influence of the school environment on academic achievement, indicated by a path coefficient value of 0.396. This coefficient is significant because the t-count value of 16.501 > t-table 1.66437 with a significance value of 0.000 < α = 0.05. This means H0 is rejected and Ha is accepted.